STRATEGIES FOR ADDRESSING DIGITAL LITERACY AND INTERNET ACCESS AS SOCIAL DETERMINANTS OF HEALTH. (11th November 2018) - Berg, K; Davis, W; Sheon, A; Newman, J; Daprano, J; Adebambo, I; Einstadter, D; Perzynski, A
Abstract: Health information technology (HIT) shows potential for increasing the value of health care. However, HIT use is lower among older adults and disadvantaged patients. We evaluated the effectiveness of a program for increasing patient portal use and internet access among underserved patients. We conducted a quasi-experimental study of a community health worker (CHW) and digital literacy program to improve patient portal use by disadvantaged patients seen at one urban primary care clinic. Patients met with a clinic-based CHW who explained patient portal use, gave referrals for a free, health-focused digital literacy training program, and identified connectivity barriers. We evaluated the program using electronic health record data (intervention vs. a control clinic) and daily CHW experience logs. In all, 186 patients met with a CHW. Of these, 2% lacked adequate English proficiency to use the portal, 18% were not interested, 26% already were using the portal and 55% expressed interest and were directed to the training program. Based on data from 6-months pre- and 6 months post-implementation, the CHW program was associated with a three-fold increase in the rate of first-time patient portal use and double the rate of portal-based visit scheduling for the intervention vs. control site (p = 0.14). Training barriers included lack of transportation, fear/anxiety of internet, and cost of internet service. Perceived benefits included ready access to lab results and proxy access to family members' health information. These results suggest that a novel clinic-based CHW program and community partnership can promote effective HIT use among disadvantaged populations.